تحديد الاحتياجات التدريبية لمعلمي الفصل في مجال طرق التدريس الفعالة في مدينة المرج وضواحيها: دراسة مقارنة - مسعود، نجية المبروك Massoud, Najiah Almabrouk (جامعة بنغازي - كلية التربية بالمرج, 2017)
تهدف الدراسة الحالية إلى معرفة الاحتياجات التدريبية وتحديدها في مجال طرق التدريس لمعلمي الفصل بمدينة المرج وضواحيها، كما تهدف للتعرف على معدل هذه الاحتياجات ومستواها، وإلى معرفة الفروق في الاحتياجات في مجال طرق التدريس بين مدارس مدينة المرج الابتدائية وضواحيها، وذلك سيؤدي للتوصل إلى نتائج تنبثق عنها توصيات تفيد المسؤلين التربويين في مجال القياس والتقويم على تصميم برامج تدريبية تخص هذه الفئة من المجتمع في مجال طرق التدريس الفعالة التي تواكب مسيرة التغير في الوقت الراهن من الناحية النظرية والعملية، من أجل العمل على تطوير المنظومة التعليمية وصقل مهارات المعلم والنهوض به في توصيل الرسالة التربوية في محتوى المواد الدراسية، وذلك في ضوء الأهداف التربوية العامة التي يتم ترجمتها إجرائيا من خلال طرق تدريس تضم في إطارها محتوى المنهج وخصائص المتعلم وقيم المهنة ومهارات المعلم، ولتحقيق ذلك تم إعداد مقياس يحتوى على مؤشرات تقيس أهداف الدراسة، تم تطبيقه من خلال دراسة وصفية، تحت بعض طرائقها، منها المسحية وذلك للتحقق من الهدف الأول والثاني، وكذلك الطريقة السببية المقارنة للتحقق من الهدف الثالث على عينة قوامها(97) من معلمي الفصل في مدينة المرج وضواحيها، وتم تحليل بيانات الدراسة من خلال أساليب إحصائية وصفية مثل الوسط المرجح كاستجابة للهدف الثاني للوقوف على أهم الاحتياجات التدريبية، وبعض أساليب الإحصاء الاستدلالي اختبار T لعينة واحد لتحليل الهدف الأول للتحقق من مستوى الاحتياجات (مرتفع أو متوسط أو منخفض) كذلك اختبار تحليل T للفروق بين متوسطين للإجابة على الهدف الثالث للتحقق من الفروق في الاحتياجات بين مدارس المرج وضواحيها وقد تم التوصل إلى النتائج التالية; توجد احتياجات تدريبية لمعلمي الفصل في المدارس الابتدائية داخل مدينة المرج وخارجها "ضواحيها " في تنمية مهارات القراءة والكتابة، وإثراء خبرات المتعلمين، واستخدام أنواع التقويم، وتنويع المثيرات لشد انتباه المتعلمين، واستخدام مهارات التفكير وتنميتها لدى المتعلمين، ومساعدة المتعلمين في البحث عن المعلومة وكيفية تنمية الفترة على الإبداع واستخدام أدوات التقويم المتنوعة، واستخدام الوسائل التعليمية - معمل المادة، واستخدام اختبارات تراعى الفروق الفردية بين المتعلمين، واستخدام كراسة المتابعة وتجميل بيئة التعلم (الفصل) لتثير انتباه المتعلمين، واختيار مصادر التعلم المتعددة.
The current study aims to find out training needs and identify them in the area of teaching methods for class teachers in the city of Al marj and its suburbs. It also aims to identify the rate and level of these needs. And to know the differences in requirements in the field of teaching methods among the elementary schools in the city of Elmarj and its suburbs. and this leads to results which leads to the recommendations enables educational officials in the area of assessment and evaluation to design training programs related to this category of the community in the field of effective teaching methods which cope with the change in current time in theory and practice, in order to develop the educational system and develop the skills of the teacher and train him to deliver his educational message in the content of academic subjects ,and this in the light of the General educational objectives that are translated in action through teaching methods and curriculum content framework and the characteristics of learner ,values of profession and the teacher skills .And to achieve that, a scale has been prepared contains indicators that measure the objectives of the study Applied through a descriptive study Under some of its methods, including surveys to verify the first and second goals , as well as the causal comparative method to verify the third goal on a sample of ( 97 ) of the class teachers in the city of Elmarj and its suburbs. The data were analyzed through descriptive statistical methods such as the weighted average in response to the second objective to identify the most important training needs, and some Inferential Statistics methods test the t one sample to analyze the first goal to verify the level of needs (high, medium or low), further analysis of the t test of the differences between two medians to answer the third objective to verify the differences in requirements among the schools in the city of Elmarj and its suburbs .And the following results were concluded: There are training needs for classroom teachers at elementary schools inside and outside Elmarj city and its suburbs for developing reading and writing ,enrichment learners 'experiences ,using types of evaluation, varying stimuli to draw learners' attention, using thinking skills and develop them among learners, helping learners to find out information, and develop the ability of creativity, using various assessment tools, using educational and instructional means-subject lab, using tests taking into consideration individual differences among learners, using follow up book note ,beautify learning context(classroom)to arouse learners' attention and selecting multiple learning resources
Keywords: الاحتياجات التدريبية -- معلم الفصل -- طرق التدريس -- مدينة المرج